Políticas educacionais e suas implicações na formação e na atuação dos professores de geografia: reflexões no contexto da rede estadual de ensino de Mato Grosso - Lima Neto, João Carlos de (2025)
In the context of neoliberal reforms of the Brazilian State, educational policies have become objects of interest and intervention, often justified by the perceived need to improve the quality of education and its indicators. Since the 1990s, the ongoing educational reform process has included a set of curricular policies that align teacher education and basic education training with the goals and guidelines established by multilateral economic organizations. More recently, with the implementation of the Common National Curriculum Base (BNCC) in basic education, the neoliberal reform of education has intensified, presenting significant challenges to the training and professional practice of Geography teachers in public schools. In this context, the main objective of this research is to understand the challenges of initial teacher education and teaching work in Geography within the ongoing curricular and educational reforms in the state school system of Mato Grosso. This is a qualitative study involving a group of seven early-career Geography teachers working in public schools in Cuiabá, Mato Grosso. Data collection was conducted through document analysis of curriculum guidelines and proposals, normative documents, educational policies, and pedagogical materials; semi-structured interviews exploring the trajectories and challenges of initial teacher education; and classroom observations of three teachers using teaching materials from a Structured Teaching System. The findings indicate that, in the field of initial teacher education, curricular and pedagogical challenges persist, including the fragmentation and dichotomy of Geography in university curricula, a disconnect between geographical and pedagogical knowledge, and a gap between teacher education institutions and basic education schools. In terms of professional practice, the challenges faced by teachers relate to deteriorating working conditions and relationships, the erosion of teacher autonomy and authorship, attacks on the teaching career, and the push for standardized pedagogical practices. Altogether, the results support the thesis that the educational and curricular policies implemented in the state school system of Mato Grosso, following the BNCC, contribute to the precarization of teacher education and professional work in basic education. They lead to the progressive erosion of teachers’ intellectual roles, autonomy, and authorship, and compromise the teaching of School Geography. As a counter-hegemonic alternative, the study advocates for challenging educational policies, reaffirming the intellectual nature of teaching, and (re)building a collective agenda of struggle and resistance.